User guide to the small N exploratory case study. RTB user guide - Almekinders, Conny J.M.; Bentley, J.W. (International Potato Center, 2020)
A qualitative study of a small number of farmers helps the research team to understand a seed system, such as local preferences for seed and varieties, and differences based on wealth, farm ecology or gender. The study should ask a few questions focused on important topics. Fifteen people per category is usually enough. Be aware of sampling bias. Review the literature and confer with colleagues before designing the interview questions. The results of the qualitative study will keep costs down by helping to design a second, quantitative study that asks the right questions of the right people.